Senam Gerak Latih Otak Untuk Mempertahankan Fungsi Keseimbangan Lansia - Marwiati Marwiati; Abdullah Azam Mustajab; Ari Setyawati (Universitas Mathla'ul Anwar Banten, 2022)
BRAIN GYM TRAINING FOR MAINTAINING BALANCE FUNCTION IN THE ELDERLY. The balance function needs to be maintained in the elderly so that he has the strength to carry out Daily Living Activities and good mobility independently. The large number of elderly people in the Adi Yuswo Purworejo Social Institution who experience disturbances in balance function, difficulty moving, mobility with the help of caregivers causes the elderly to become deficit self-care. To reduce self-care deficits in the elderly, do brain training exercises. The purpose of the Brain Training Motion Gymnastics training activity is to maximize sensory and motor coordination functions in the elderly. Brain Training Movement activities are carried out for 3 weeks with a frequency of 3 times and a duration of 30-45 minutes at the Adi Yuswo Purworejo Social Institution. The results achieved by as many as 12 elderly people can optimally gait and balance function from being mobility assisted now to being independent. Brain Exercise Movements have proven to be effective in optimizing gait balance in the elderly.